2004
DOI: 10.1007/s00223-003-0105-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density of the Lumbar Spine is Associated with TNF Gene Polymorphisms in Early Postmenopausal Japanese Women

Abstract: We investigated the relationships between tumor necrosis factor (TNF) gene polymorphism, circulating TNF-alpha (TNF-alpha) concentrations, and bone mineral density (BMD) in the lumbar spine. TNF gene polymorphisms studied were the Nco I polymorphism within the first intron of TNF-beta (TNF-beta) and three single nucleotide polymorphisms in the promoter region of the TNF-alpha gene, at positions -857, -863, and -1031. Allelic variants of the TNF gene were identified using restriction fragment length polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Prior studies found that the SNPs in TNF-α gene are related to osteoporosis in elderly people [1520]. Moreover, the allelic variants of the TNF-α gene and BMD, including those between SNPs rs1800630 (-863C/A) and rs1800630 (-1031T/C) of the TNF-α gene and low BMD [16, 17] are associated to a dinucleotide repeat polymorphism in TNF-α for linkage to osteoporosis [21]. The TNF-α gene may have joint and interactive effects with LEPR in osteoporosis development [11, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies found that the SNPs in TNF-α gene are related to osteoporosis in elderly people [1520]. Moreover, the allelic variants of the TNF-α gene and BMD, including those between SNPs rs1800630 (-863C/A) and rs1800630 (-1031T/C) of the TNF-α gene and low BMD [16, 17] are associated to a dinucleotide repeat polymorphism in TNF-α for linkage to osteoporosis [21]. The TNF-α gene may have joint and interactive effects with LEPR in osteoporosis development [11, 20].…”
Section: Introductionmentioning
confidence: 99%